Problems Regarding the Fitness for Trial in Thailand: A Comparative Study with the Jurisdiction of England and Wales, and the Netherlands - Dejchai, Yada (Nitipat NIDA Law Journal, 2022)
This paper conducts a study regarding the fitness for trial test in Thailand, through a comparative study with the jurisdictions of England and Wales, the Netherlands and the proposal of Law Commission of England and Wales. This paper aims to propose suggestions to amend the law of Thailand regarding the fitness for trial test as well as regulations related to it. This research found that the law of England and Wales and the proposal of the Law Commission of England and Wales had a solid fitness for trial test as well as the regulations regarding the handling of those who found unfit for trial. Ultimately, this paper suggested that the law of England and Wales and the proposal of the Law Commission of England and Wales should be used as models to reform the fitness for trial test and regulation relating to the fitness for trial test in Thailand. Additionally, this paper made a proposal for a new statutory test and regulations relating to fitness for trial to be amend in the Criminal Procedure Code.